2017
DOI: 10.1111/acps.12756
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical correlates of insomnia in adults with attention‐deficit hyperactivity disorder

Abstract: Brevik EJ, Lundervold AJ, Halmøy A, Posserud MB, Instanes JT, Bjorvatn B, Haavik J. Prevalence and clinical correlates of insomnia in adults with attention-deficit hyperactivity disorder Objective: To investigate the prevalence of insomnia in adults with Attention-deficit hyperactivity disorder (ADHD) and its association with clinical subtypes, current ADHD symptoms, and stimulant treatment. Method: We obtained diagnostic information, symptom rating scales and treatment history from clinically ascertained adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 31 publications
(42 reference statements)
4
34
2
Order By: Relevance
“…In line with this, as many as 61.5% of ADHD patients reported having used hypnotics, which was three times more often than among controls. We recently published data on insomnia in this sample, showing that 66.8% of the ADHD patients compared with 28.8% of the controls fulfilled the DSM-IV criteria for insomnia disorder (Brevik et al, 2017 ). These findings clearly indicate that sleep problems are common and clinically severe among adults with ADHD, and corroborate findings from other studies (Surman et al, 2009 ; Fisher et al, 2014 ; Hvolby, 2015 ; Instanes et al, 2016 ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In line with this, as many as 61.5% of ADHD patients reported having used hypnotics, which was three times more often than among controls. We recently published data on insomnia in this sample, showing that 66.8% of the ADHD patients compared with 28.8% of the controls fulfilled the DSM-IV criteria for insomnia disorder (Brevik et al, 2017 ). These findings clearly indicate that sleep problems are common and clinically severe among adults with ADHD, and corroborate findings from other studies (Surman et al, 2009 ; Fisher et al, 2014 ; Hvolby, 2015 ; Instanes et al, 2016 ).…”
Section: Discussionmentioning
confidence: 80%
“…The data were collected between 2011 and 2015. More details about the study can be found elsewhere (Brevik et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…189 Insomnia occurs in 55% to 80% of adults with ADHD, with the combined ADHD subgroup showing higher rates of insomnia than the inattentive subgroup. 190 Initial insomnia is a frequent side effect when starting an ADHD medication, although patients may experience an improvement in sleep quality with appropriate treatment over time. [191][192][193][194] In our experience, a medication with too long of a duration may exacerbate insomnia for some individuals, while, for others, a formulation with a small amount of medication released in the early evening may help to calm the brain, decrease restlessness, and improve sleep quality.…”
Section: Depressionmentioning
confidence: 99%
“…Mood disorders and anxiety disorders are common in both men and women across all age groups Fayyad et al, 2016). Adult ADHD is also associated with sleep problems, especially insomnia (Brevik et al, 2017), which are well-known risk factors for increased risk of somatic health problems: e.g. being overweight, developing Type 2 diabetes or cardiovascular disease, and premature death in the general population (Clark et al, 2016;Ikehara et al, 2009;Medic, Wille, & Hemels, 2017).…”
Section: Introductionmentioning
confidence: 99%